Factors predicting quality of nursing care among nurses in tertiary care hospitals in Mongolia. (12th February 2019) - Gaalan, K.; Kunaviktikul, W.; Akkadechanunt, T.; Wichaikhum, O.‐A.; Turale, S.
Abstract : Background: An increasing nursing shortage, high workloads and poor working environments are affecting the quality of nursing care in many countries including Mongolia. Aim: To explore the level of quality of nursing care, nursing competency and nursing practice environment, as well as the predictability of nurses' personal factors, nursing competency and nursing practice environment on quality of nursing care as perceived by nurses in Mongolia. Methods: We collected data from 346 registered nurses, randomly selected and working in seven general public tertiary care hospitals in the capital city of Ulaanbaatar, and four regions of Mongolia. Instruments used were the Good Nursing Care Scale, the Competency Inventory for Registered Nurses and the Practice Environment Scale of Nursing Work Index. Data were analysed using descriptive statistics and multiple regression analysis. Results: The overall quality of nursing care and nursing competency was perceived to be at a high level, whereas nursing practice environment was at a favourable level. Nursing competency and nursing practice environment were found as significant predictors of nursing care quality, while personal factors were found as non‐significant predictors. Discussion: Improving nursing competency and practice environment enhances the quality of nursing care. However, a study limitation is that self‐reporting may not have reflected the accuracy of variables. Conclusion: Findings provide important evidence for the use of measures and strategies to enhance the quality of nursing care by improving nursing competency and the nursing practice environment. Implications for nursing and health policy: Policymakers, administrators and nurses need to work together to develop and implement policies to enhance and support the competency and practice environments of the Mongolian nurses.